The Meaning of Visual Elements of Hotel Advertisements on New Normal Era - Ni Wayan Kasni; I Wayan Budiarta (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
The situation of Covid-19 Pandemic which happened in the world have brought a very big impact to the life of the people. This also brought a big impact of tourism in Bali in which the life of people in Bali depends on the tourism a lot. Therefore, some big hotels try to find to various strategies to fasten the recovery of tourism in Bali. Some of them are promoting their hotels which guarantee that the guests are safe when they are staying in the hotels. Besides, they also create innovative package advertisements to attract the guests. This makes me interested in making the research on The Meaning of Visual Elements of Hotel Advertisements on New Normal Era. This research is focused on two problems, namely (1) what visual elements are used on the hotel advertisements and (2) what are their meanings. The data were taken from some of the hotels around Sanur and analysed by using semiotic theory. The results of the analysis revealed that the visual elements used are pictures of food, drinks, and some other objects related with the application of health protocol such as, mask, wash basin, soap, hand sanitizer, disinfectant, temperature gun, face shield, and the like. All them convey affected meaning in this case to influence the readers to buy the products or to come and stay in the hotels promoted.